Cardiovascular risk scores do not account for the effect of treatment: a review. - Liew, S.M.; Doust, J.; Glasziou, P. (2011)
The use of risk-factor-modifying drugs-for example, statins-and disease-modifying medication-for example, platelet inhibitors-was not accounted for. In addition, none of the risk scores addressed the effect of treatment drop-ins-that is, treatment started during the study period. Ideally, a risk score should be derived from a population free from treatment. The lack of accounting for treatment effect and the wide variation in study characteristics, predictors and outcomes causes difficulties in the use of cardiovascular risk scores for clinical treatment decision.